Utilizing Visual Grammar Cues to Support Students’ Writing in the Simple Present Tense - Gita Christ Natalia Faidiban; Nurteteng (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores the effectiveness of visual grammar cues in enhancing students’ ability to write using the simple present tense. The research was conducted at MTs Muhammadiyah 1 Salawati and involved 22 eighth-grade students. The objective was to determine whether visual grammar-based instruction could improve students’ grammar mastery in writing, particularly in understanding and applying the simple present tense. Using a pre-experimental design with a one-group pre-test and post-test approach, students’ writing performance was measured before and after the intervention. Data were analyzed using SPSS version 25.0, specifically the Paired Sample T-Test, to determine statistical significance. The results revealed a notable improvement in students’ scores from an average of 54.77 on the pre-test to 76.86 on the post-test with a significance value of 0.00 (p < 0.05). These findings indicate that the use of visual grammar cues significantly supports students’ comprehension and usage of grammar rules in writing. The implications suggest that visual grammar is a promising instructional strategy, particularly for visual learners, as it simplifies abstract grammatical concepts into more concrete and engaging forms. In conclusion, incorporating visual grammar cues into English instruction can be an effective method to improve students' mastery of verb tenses and sentence structure in writing.